Monitoring Adverse Effects of Antipsychotics and Antidepressants: A Population Based Study - Rallabandi, Satya Sree; Makula, Sai Samanth; Sindgi, Vasudeva Murthy; Babu, Bandari Jagadeesh; Puneem, Usha Sree (Journal of Pharmacy Practice and Community Medicine)
Aim: To monitor the nature and incidences adverse effects of both antipsychotics and antidepressants medicines in the psychiatry outpatient department. Objectives: Reporting the incidences of adverse effects and to establish the frequency of a specific class of drug. Identifying the system affected and the assessment of the management of the adverse effects by the physician. For the study, we have adopted Global Assessment Scale (GAS), Simpson-Angus Extra pyramidal Side Effects Scale (SAS) and The Antidepressant Side-Effect Checklist (ASEC). Materials and Methods: A prospective cohort study carried out in the psychiatry out-patient department. All the patients attending psychiatry outpatient department enrolled based on the pre-specified inclusion criteria and monitored for adverse effects. Causality also assessed by WHO-UMC causality assessment system and Naranjo Causality Assessment. Results: The incidence rate of adverse effects (46.07%) and 560 adverse effects documented. Weight gain (n=29, 9.2%) followed by drowsiness (n=27, 4.82%) are most commonly reported adverse effects. Atypical antipsychotics (n=279, 49.82%) were the most common class of psychotropic drugs implicated in adverse effects. Escitalopram (n=93, 37.80%) followed by olanzapine (n=53, 21.54%) associated with a maximum number of adverse effects. Central nervous system (n=225, 40.17%) was the most affected organ system followed by gastrointestinal system (n=130, 23.21%). Conclusion: Study revealed moderate incidences of adverse effects in patients attending the psychiatry outpatient department. Majority of the adverse effects reported during the study were mild in nature and not preventable. The role of a clinical pharmacist clearly elucidated regular intensive monitoring of adverse effects may improve the quality of patients’ care, reduction in the treatment cost and augmentation of the medication adherence among patients.
Keywords: Adverse effects; Pharmacovigilance; Antipsychotics; Antidepressants; Extra pyramidal side effects.